Pengaruh Penggunaan Media Dadu Pancasila Terhadap Hasil Belajar Pendidikan Pancasila Siswa Kelas III SDN 15 Mataram - Fatimatuz Zahra; Muhammad Makki; Khairun Nisa (Action Research Journal, 2025)
This study aims to determine the effect of using the Pancasila Dice learning media on the learning outcomes of Civics Education (Pendidikan Pancasila) among third-grade students of SDN 15 Mataram. The background of this research is based on the low learning outcomes of students and the lack of variety in learning media used by teachers, resulting in students’ low enthusiasm during the learning process. The Pancasila Dice was developed as an alternative interactive and enjoyable learning medium by combining visual elements, games, and active student participation. This research employed a quantitative approach with an experimental method using a Quasi-Experimental Design, specifically the Posttest Only Control Group Design. The population consisted of all third-grade students of SDN 15 Mataram in the 2025/2026 academic year, totaling 42 students. The sampling technique used was saturated sampling, in which all members of the population were included as the research sample. The research instrument was a multiple-choice test measuring students’ learning outcomes. Data were analyzed using the Mann-Whitney U Test. The results showed a significant difference between the learning outcomes of students in the experimental class, which used the Pancasila Dice media, and those in the control class, which did not. The Mann-Whitney U test yielded an Asymp. Sig. (2-tailed) value of 0.027 < 0.05, indicating that the use of Pancasila Dice had a positive effect on students’ Civics Education learning outcomes. Therefore, the use of Pancasila Dice is effective in improving learning outcomes and can serve as an attractive, interactive, and suitable alternative learning medium for elementary school students